Some characteristics of snow-cover in upper Beas catchment - UPADHYAY, DS; KANT, RAJNI; CHOWDHURY, JN; KATYAL, KN (MAUSAM, 1985)
The snow cover data collected during snow-survey 1981 in upper Beas watershed have been utilized to assess the thermal quality of existing snow cover and to compute snow-melt quantities for the sub-catchments of Solang and upper Beas above Kothi (2680 m approx) A brief survey of snow-cover in upper Beas basin above Manali has also been described.